Pediatric foreign body aspiration: How much does our community know? - Singh Aprajita; Ghosh Dhruv; Samuel Clarence; Bhatti William (Wolters Kluwer Medknow Publications, 2010)
Aims: Foreign body aspiration (FBA) is one of the main causes of accidental death in childhood. This study was designed to evaluate the level of awareness of FBA and its resultant dangers in the community. Materials and Methods: Sixty-three primary caregivers were interviewed about their awareness of FBA, its attendant dangers, preventive measures taken, and how will they take care of a child in the event of a FBA according to an agreed protocol. Results: Awareness levels about FBA were abysmally low in the population that was studied. Twenty-five percentage of the study population had not heard about this condition, and 46% could not recognize a FBA if it happened. Also, 76% of the study group did not know about the attendant dangers of this condition. Conclusions: There is a dire need to spread awareness about both prevention and treatment of this morbid condition. Health care professionals need to increase their efforts to spread more knowledge in the community about FBA.